1975
DOI: 10.1203/00006450-197509000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Growth Hormone, Insulin, and Glucagon Responses to Arginine Infusion in Children and Adolescents with Idiopathic Short Stature, Isolated Growth Hormone Deficiency, Panhypopituitarism, and Anorexia Nervosa

Abstract: ExtractThe effects of intravenous infusion of arginine (20 g/m2) after an overnight fast on plasma immunoreactive growth hormone (GH), insulin (IRI), and glucagon (IRG), and blood glucose were examined in five groups of children and adolescents: 10 normal individuals, 18 with idiopathic short stature, 6 with isolated growth hormone deficiency, 8 with panhypopituitarism, and 6 with anorexia nervosa.The mean fasting plasma GH concentration was significantly elevated in the group with anorexia nervosa (P < 0.05),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

1978
1978
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…These results suggest that reduction in body weight and malnutrition appear to be major cau¬ sative factors of the observed pancreatic -cell dys¬ function. On the other hand, the glucagon re¬ sponse to arginine loading in patients with anore¬ xia nervosa was not significantly different from that in the control group and is consistent with previous reports (Sizonenko et al 1975;Blickle et al 1984). The difference in glucagon responses to the two different stimuli suggests that the -cell in anorectic patients is selectively unresponsive to a reduction in glucose concentrations, whereas the response to amino acid stimuli appears to be in¬ tact.…”
Section: Discussionsupporting
confidence: 91%
“…These results suggest that reduction in body weight and malnutrition appear to be major cau¬ sative factors of the observed pancreatic -cell dys¬ function. On the other hand, the glucagon re¬ sponse to arginine loading in patients with anore¬ xia nervosa was not significantly different from that in the control group and is consistent with previous reports (Sizonenko et al 1975;Blickle et al 1984). The difference in glucagon responses to the two different stimuli suggests that the -cell in anorectic patients is selectively unresponsive to a reduction in glucose concentrations, whereas the response to amino acid stimuli appears to be in¬ tact.…”
Section: Discussionsupporting
confidence: 91%
“…Insulin measurements after provocation tests with various stimuli have been published by several authors [34,128,129,251,265,317]. The results of Youlton et al [317] were ambiguous, especially since the control values were not given.…”
Section: Insulinmentioning
confidence: 95%
“…The results of Youlton et al [317] were ambiguous, especially since the control values were not given. Sizonenko et al found reduced responses to arginine, but no statistically significant differences [265]. Karp et al [128] tested 190 patients with arginine, of whom 80 exhibited a diminished insulin response, compared to healthy controls.…”
Section: Insulinmentioning
confidence: 97%
See 1 more Smart Citation
“…In der Literatur wurden bei Kindern mit GH-Mangel sowohl basal als auch 60 und 90 min nach dem Ende einer Arginininfusion signifikant niedrigere Blutzuckerwerte als bei gesunden Altersgenossen gemessen [4,6,15,17]. Somit scheinen diese Kinder sensibler auf Arginin zu reagieren und sind wohl gefährdeter, symptomatische Hypoglykämien zu entwickeln.…”
Section: Diskussionunclassified